BRAF mutations are associated with increased iron regulatory protein‐2 expression in colorectal tumorigenesis. Issue 6 (2nd June 2017) - Horniblow, Richard D.; Bedford, Matthew; Hollingworth, Robert; Evans, Sarah; Sutton, Emily; Lal, Neeraj; Beggs, Andrew; Iqbal, Tariq H.; Tselepis, Chris
Abstract : A role for iron in carcinogenesis is supported by evidence that iron metabolism proteins are modulated in cancer progression. To date, however, the expression of iron regulatory protein‐2 (IRP2), which is known to regulate several iron metabolism proteins, has not been assessed in colorectal cancer. Expression of IRP2 was assessed by quantitative RT‐PCR and immunohistochemistry in human colorectal cancer tissue. By interrogating The Cancer Genome Atlas (TCGA) database, expression of IRP2 and transferrin receptor‐1 (TfR1) was assessed relative to common mutations that are known to occur in cancer. The impact of suppressing IRP2 on cellular iron metabolism was also determined by using siRNA and by using the MEK inhibitor trametinib. IRP2 was overexpressed in colorectal cancer compared to normal colonic mucosa and its expression was positively correlated with TfR1 expression. In addition, IRP2 expression was associated with mutations in BRAF . The MEK inhibitor trametinib suppressed IRP2 and this was associated with a suppression in TfR1 and the labile iron pool (LIP). Moreover, epidermal growth factor stimulation resulted in decreased ferritin expression and an increase in the LIP which were independent of IRP2. Results presented here suggest that ablating IRP2 provides a therapeutic platform for intervening in colorectal tumorigenesis. Abstract : IRP‐2 is overexpressed in colorectal cancer and that its expression is tightly correlated with transferrin receptor‐1 expression. Furthermore, IRP‐2 expression is associated with mutation in BRAF. Using MAPK/ERK inhibitors might be another mechanism by which iron sensitive tumours can be targeted.